Breaking the frame: evolving practices of first-generation photo-elicitation researchers. Issue 1 (15th March 2022) - Dam, S.C.
Abstract : This article examines first-generation social scientists' uses and understandings of photo-elicitation practices as they evolved over time and experiences. Participants have extensive experience with photo-elicitation in their own visual research practices. The research included speaking with respected visual researchers Doug Harper, Eric Margolis, Gillian Rose, and Dona Schwartz. As participants in a larger research project, they each take up photo-elicitation over video conferencing in unique and varied ways expanding what photo-elicitation means and is capable of achieving as a visual research method. The wider research project used photo-elicitation over Skype as an approach to expand traditional face-to-face sessions producing trustworthy, in-depth data and indicated that photographic practices by social scientists evolve but also carry disciplinary traditions, expectations, and practices. This paper documents some historical developments of first-generation photo-elicitation researchers demonstrating that practices are not static but can transform and contribute to co-creating new meanings, are open to unexpected developments, and accommodating new approaches as they arise. Practices based on first-generation researchers continue to influence and evolve visual research practices.